2021
DOI: 10.1177/12034754211035667
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes of IL-17 Inhibitors in Hidradenitis Suppurativa: A Systematic Review

Abstract: The IL-17 pathway is a potential therapeutic target shown to be implicated in hidradenitis suppurativa (HS), however, it remains unclear whether evidence from mechanistic studies may translate into clinical practice. This systematic review summarizes available treatment outcomes of IL-17 inhibitors in patients with HS. Embase, MEDLINE, PubMed, and clinicaltrials.gov were comprehensively searched on February 26, 2021 to include 16 original studies representing 128 patients with HS (mean age: 36.5 years; age ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 52 publications
(83 reference statements)
1
28
0
Order By: Relevance
“…Hidradenitis suppurativa, a chronic inflammatory skin disease of hair follicles, is characterized by substantial skin infiltration of T H 17 cells that express CD161, a lineage marker for T H 17 cells 135 . Open-label pilot clinical trials with secukinumab showed moderate efficacy in patients with hidradenitis suppurativa 136 , and phase III trials are ongoing. Although secukinumab was not effective in treating alopecia areata 137 , there is off-label use of IL-17-blocking drugs for the treatment other skin disorders, including Behcet disease, lichen planus, pustular psoriasis, impetigo herpetiformis and pityriasis rubra pilaris.…”
Section: Il-17 In Autoimmunity and Inflammationmentioning
confidence: 99%
“…Hidradenitis suppurativa, a chronic inflammatory skin disease of hair follicles, is characterized by substantial skin infiltration of T H 17 cells that express CD161, a lineage marker for T H 17 cells 135 . Open-label pilot clinical trials with secukinumab showed moderate efficacy in patients with hidradenitis suppurativa 136 , and phase III trials are ongoing. Although secukinumab was not effective in treating alopecia areata 137 , there is off-label use of IL-17-blocking drugs for the treatment other skin disorders, including Behcet disease, lichen planus, pustular psoriasis, impetigo herpetiformis and pityriasis rubra pilaris.…”
Section: Il-17 In Autoimmunity and Inflammationmentioning
confidence: 99%
“…While data are increasing regarding secukinumab and brodalumab, the literature on ixekizumab is limited [4, 6-8]. Ixekizumab, a humanized monoclonal immunoglobulin G 4 antibody, specifically binding to IL-17A, is very effective in treating moderate to severe psoriasis [4]. We found 3 case reports of ixekizumab for HS.…”
Section: Discussionmentioning
confidence: 99%
“…The IL-17 pathway has been implicated as a potential therapeutic target in HS, prompting clinical trials with various IL-17 inhibitors (secukinumab, brodalumab, and ixekizumab) [4]. While data are increasing regarding secukinumab and brodalumab, the literature on ixekizumab is limited [4,[6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations